Scanning Electrochemical Microscopy of Cytochrome c Peroxidase through the Orientation‐Controlled Immobilisation of Cytochrome c. Issue 7 (31st May 2016) - Gunawan, Christian A.; Nam, Ekaterina V.; Marquis, Christopher P.; Gooding, J. Justin; Thordarson, Pall; Zhao, Chuan
Abstract: Immobilisation of enzymes onto surfaces with defined orientation is of particular importance in order to optimise their activity and capacity to dock electron‐transfer partners. Local characterisation methods are thus crucial to understanding the activity–orientation relationship of immobilised enzymes for long‐term storage and applications. Herein, cytochrome  c (cyt  c ) is chemoselectively immobilised through a cysteine functional group with a maleimide‐functionalised gold surface, thus controlling cyt  c orientation. X‐ray photoelectron spectroscopy confirmed successful cyt  c immobilisation. Scanning electrochemical microscopy methodologies were developed to quantify the activity of immobilised cyt  c and cytochrome  c peroxidase (C c P). The results suggest optimal enzymatic activities and docking ability for surface‐tethered cyt  c are obtained through the cysteine–maleimide linkage, in comparison to conventional indiscriminate lysine–carboxyl linkages. This study reveals the strong influence of cyt  c orientation, as a result of linking strategy, upon the docking ability of redox‐electron partner C c P. Abstract : Orientation and partner : Scanning electrochemical microscopy reveals that site‐specific immobilization of cytochrome  c is the key to effective docking and electron transfer to its native electron‐transfer partner, cytochrome  c peroxidase.